2021
DOI: 10.3389/fpsyg.2020.569581
|View full text |Cite
|
Sign up to set email alerts
|

Home Literacy Environment and Children’s English Language and Literacy Skills in Hong Kong

Abstract: Emerging evidence has shown a positive association between the home literacy environment (HLE) and monolingual children’s language and literacy development. Yet, far fewer studies have examined the impact of the HLE on second language development. This study examined relations between the HLE and children’s development of English as a second language in Hong Kong. Participants were 149 ethnic Chinese children (80 girls; Mage = 59 months, SDage = 10 months) and one of their caregivers. Caregivers completed ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 93 publications
3
6
0
Order By: Relevance
“…Such an environment allows the inputs, which are children, to play and interact with books, objects, and role models for enhanced English learning outcomes seen as outputs. This finding echoed a previous conclusion that the home literacy environment was differentially associated with letter knowledge, English vocabulary, reading skills, and phonological awareness (Lau & Richards, 2021). Consequently, exposing children to homeschooling allows them to experience such differentiation in English language learning.…”
Section: Discussionsupporting
confidence: 82%
“…Such an environment allows the inputs, which are children, to play and interact with books, objects, and role models for enhanced English learning outcomes seen as outputs. This finding echoed a previous conclusion that the home literacy environment was differentially associated with letter knowledge, English vocabulary, reading skills, and phonological awareness (Lau & Richards, 2021). Consequently, exposing children to homeschooling allows them to experience such differentiation in English language learning.…”
Section: Discussionsupporting
confidence: 82%
“…On the contrary, during English reading, parents value linguistic aspects like acquisition of vocabulary and pronunciation much more than cultural aspects. Our findings echo previous literature that Chinese parents emphasize schoolrelated skills and adopt didactic approaches in English literacy activities (Lau and Richards, 2021).…”
Section: Language Ideology: Between Global Value and Local Identitysupporting
confidence: 91%
“…Recent research showed that most immigrant parents support bilingual education (Chang, 2008;Wei, 2011;Lau and Richards, 2021).…”
Section: Parental Perceptions Of Bilingualism and Home Language Devel...mentioning
confidence: 99%
“…Recent research showed that most immigrant parents support bilingual education ( Chang, 2008 ; Wei, 2011 ; Lau and Richards, 2021 ). Their reasons are focused on the hope that their children can develop a sense of national identity with their cultural roots, be able to communicate in the home language with older generations, and gain more job opportunities when they enter society (e.g., Tseng and Fuligni, 2000 ; Lao, 2004 ; Surrain, 2021 ; Hwang et al, 2022 ).…”
Section: Parental Perceptions Of Bilingualism and Home Language Devel...mentioning
confidence: 99%